Assessing the use of cell phones to monitor health and nutrition interventions: Evidence from rural Guatemala - Ceballos, Francisco; Hernandez, Manuel A.; Olivet, Francisco; Paz, Cynthia (Public Library of Science, 2020)
In-person (face-to-face) data collection methods offer many advantages but can also be time-consuming and expensive, particularly in areas of difficult access. We take advantage of the increasing mobile phone penetration rate in rural areas to evaluate the feasibility of using cell phones to monitor the provision of key health and nutrition interventions linked to the first 1,000 days of life, a critical period of growth and development. We examine response rates to calendarized text messages (SMS) and phone calls sent to 1,542 households over a period of four months. These households have children under two years old and pregnant women and are located across randomly selected communities in Quiche, Guatemala. We find that the overall (valid) response rate to phone calls is over 5 times higher than to text messages (75.8% versus 14.4%). We also test whether simple SMS reminders improve the timely reception of health services but do not find any effects in this regard. Language, education, and age appear to be major barriers to respond to text messages as opposed to phone calls, and the rate of response is not correlated with a household’s geographic location (accessibility). Moreover, response veracity is high, with an 84–91% match between household responses and administrative records. The costs per monitored intervention are around 1.12 US dollars using text messages and 85 cents making phone calls, with the costs per effective answer showing a starker contrast, at 7.76 and 1.12 US dollars, respectively. Our findings indicate that mobile phone calls can be an effective, low-cost tool to collect reliable information remotely and in real time. In the current context, where in-person contact with households is not possible due to the COVID-19 crisis, phone calls can be a valuable instrument for collecting information, monitoring development interventions, or implementing brief surveys.